2012
DOI: 10.1039/c2sm25426c
|View full text |Cite
|
Sign up to set email alerts
|

Structural model for α-synuclein fibrils derived from high resolution imaging and nanomechanical studies using atomic force microscopy

Abstract: A number of proteins form supramolecular protein aggregates called amyloid fibrils which selfassemble under appropriate conditions. We have used high-resolution atomic force microscopy to obtain detailed ultrastructural information on fibrils formed from the E46K mutant of the human asynuclein protein, which is associated with Parkinson's disease. Two distinct fibril species were found; one with a height of 6.0 nm exhibiting no periodicity along its length, and the other with 7.4 nm height, revealing a periodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 55 publications
(77 reference statements)
4
29
2
Order By: Relevance
“…5A, panel d). Our group and others reported previously that the height of ␣-Syn mature fibrils is within the 6 -9-nm range (30). Thus, it is likely that the first population corresponded to protofilament species, whereas the second one represented a more mature fibril species but not the final state of ␣-Syn assembly because mature ␣-Syn fibrils are composed of four protofilaments (31).…”
Section: The H50q Mutation Induces Little Perturbation Of ␣-Synmentioning
confidence: 96%
“…5A, panel d). Our group and others reported previously that the height of ␣-Syn mature fibrils is within the 6 -9-nm range (30). Thus, it is likely that the first population corresponded to protofilament species, whereas the second one represented a more mature fibril species but not the final state of ␣-Syn assembly because mature ␣-Syn fibrils are composed of four protofilaments (31).…”
Section: The H50q Mutation Induces Little Perturbation Of ␣-Synmentioning
confidence: 96%
“…263 Though not substantiated, such non-circular packing of monomers could also hold true for other β-sheet folded proteins. 261, 263 In addition, curly αS fibrils prepared by filtration-like steps during aggregation possessed a persistence length of 170 nm, while straight αS fibrils from unperturbed aggregation displayed persistence lengths of up to 140 μm. 264 …”
Section: Alpha-synuclein and Parkinson’s Diseasementioning
confidence: 99%
“…241 A hierarchical assembly model (HAM) was proposed by Inonescu-Zanetti et al 254 to describe the architecture of immunoglobulin light-chain protein SMA fibrils assembled from smaller subspecies and has shown general applicability to the nanoscale assemblies of Aβ, αS and IAPP as well as SH3 domain, lysozyme, SMA, β 2 -microglobulin and beta-lactoglobulin. 142, 251, 252, 255260 Alternatively, a new packing model was proposed by Sweers et al, 261 in attempt to reconcile the morphological and mechanical data observed for two distinct fibril species of E46K, a mutant of αS. Nonetheless, according to the HAM, protofilaments are established by the nucleated polymerization kinetic model, in which the protofilaments elongate by the addition of monomeric, partially folded intermediates to their growing ends.…”
Section: Alpha-synuclein and Parkinson’s Diseasementioning
confidence: 99%
“…This enables to study the morphological conformation of the heterogeneous and polymorphic species present during the process of amyloid aggregation, such as monomeric proteins, oligomers, protofibrillar structures and the final mature amyloid fibrils (Fig. 8 ) [8, 14, 148, 149]. It has been shown that AFM, though at the limit of its resolution (objects with smaller height than < 1 nm), is capable to visualize the species present during the lag-phase of the aggregation.…”
Section: Single Molecule Investigation By Atomic Force Microscopy Tecmentioning
confidence: 99%
“…Therefore, the study of the statistical mechanics properties of polymers by means of the measurement of the persistence l p has been a valuable route towards understanding the nanoscale mechanics of polymers and other linear structures enabling to measure their intrinsic stiffness [148, 149, 170]. However, a limiting step in the measurements of the intrinsic Young’s modulus of amyloid fibrillar aggregates on a surface is the correct evaluation of the cross-sectional moment of inertia I [148].…”
Section: Single Molecule Investigation By Atomic Force Microscopy Tecmentioning
confidence: 99%